2022
DOI: 10.1097/md.0000000000028994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound Danshen dropping pills on adverse cardiovascular events and quality of life after percutaneous coronary intervention in patients with coronary heart disease

Abstract: Background: Percutaneous coronary intervention (PCI) is an important means for the treatment of coronary atherosclerotic heart disease and has effectively reduced the mortality of coronary heart disease. However, reperfusion can also cause certain damage to the vascular endothelium, leading to the major adverse cardiovascular events. Compound Danshen dropping pill is a Chinese patent medicine preparation. At present, many studies have evaluated the effect of compound Danshen dropping pill in reducing the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…CDDP can inhibit platelet aggregation, reduce inflammation and damage of vascular endothelium. At present, a number of studies have evaluated the reduction of CDDP in the incidence of cardiovascular adverse events after PCI ( 42 ). Rong Y et al observed that CDDP preconditioning could decrease the incidence of CIN in patients with PCI.…”
Section: Discussionmentioning
confidence: 99%
“…CDDP can inhibit platelet aggregation, reduce inflammation and damage of vascular endothelium. At present, a number of studies have evaluated the reduction of CDDP in the incidence of cardiovascular adverse events after PCI ( 42 ). Rong Y et al observed that CDDP preconditioning could decrease the incidence of CIN in patients with PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Acute coronary artery occlusion is often associated with atherosclerosis and plaque rupture, leading to myocardial ischemia or even infarction ( Mehta et al, 2022 ). An enormous number of laboratory and clinic studies have shown that a series of formulas based on the DSF can improve cardiac function and morphology after acute myocardial infarction, indicating a promising myocardial protective effect of DSF ( Lv et al, 2022 ; Sun and Zhang, 2022 ; Xu et al, 2022 ). Several studies have demonstrated that DS (either as a prodrug or as the formulation) has a beneficial effect on the heart during the pathological process of atherosclerosis both at progression stage and acute exacerbation stage ( Liu et al, 2022c ).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…There are numerous records about the use of natural plants, animals, and minerals to treat diseases in the classics of traditional Chinese medicine, and these materials are collectively referred to as Traditional Chinese Medicine (TCM) ( Ai et al, 2023 ). Traditional Chinese Medicine has constructed the foundations of a sophisticated traditional medical system through thousands of years of medication discovery, experience accumulation as well as knowledge preservation, and served as a safeguard for the health of the Chinese since ancient times ( Lv, R. et al, 2022 ; Zhang et al, 2023 ). In the past few decades, as a result of the increased attention given to TCM around the world, it has become an increasingly essential healthcare system not just in China but also globally, which may stably provide innovative therapies for patients with life-threatening diseases in the modern society ( Xing and Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…They may increase the precision of classification approaches and aid in the execution of both classification and prediction models, which are carried out using the Python programming language. The heart prediction system may be used by medical professionals to enhance service quality by using data mining expertise to give a method for identifying hidden patterns in the data [18]- [20].…”
Section: Introductionmentioning
confidence: 99%